MODEL STRATEGI START-UP BUSINESS SEBAGAI UPAYA OPTIMALISASI POTENSI EKONOMI DESA WISATA DALAM MENDUKUNG DIGITAL ECONOMY NASIONAL PADA KEWIRAUSAHAAN DI KABUPATEN SAMOSIR - Sumaizar Sumaizar; Novendra Adisaputra Sinaga; Eka Pratiwi Septania Parapat (Jurnal Ekonomi dan Bisnis (EK dan BI), 2023)
The urgency of this research is to analyze the implementation of the Start-Up Business Strategy to optimize the economic potential of tourism villages in supporting the national Digital Economy in entrepreneurship in Samosir Regency. The results of the analysis of the implementation of the Start-Up strategy will become a formulation of a strategy that can be used to explore entrepreneurial potential in Samosir Regency. Implementing the Start-Up Strategy is the starting point for the growth of new businesses that have the potential to progress. The emergence of new business opportunities and ideas through a start-up strategy can explore and optimize the village's economic potential, especially entrepreneurship, which has so far been invisible. Adopting technology is one of the best solutions to improve business performance even in the midst of a global crisis. The purpose of this research is to analyze and formulate the implementation of the Start-Up Business Strategy as an Effort to Optimize the Economic Potential of Tourism Villages in supporting the National Digital Economy in Entrepreneurship in Samosir Regency. The results of this research are an analysis and strategy regarding the application of Start Up businesses to improve the digital economy.